Periodic solutions of periodic generalized food limited model - Yongkun Li (International Journal of Mathematics and Mathematical Sciences)
By using the continuation theorem of coincidence degree theory, the existence of positive periodic solutions for a periodic generalized food limited model with state dependent delays and distributed delays is studied, respectively.